2019
DOI: 10.1002/asi.24111
|View full text |Cite
|
Sign up to set email alerts
|

Semantic web or web of data? a diachronic study (1999 to 2017) of the publications of tim berners‐lee and the world wide web consortium

Abstract: The web has been, in the last decades, the place where information retrieval achieved its maximum importance, given its ubiquity and the sheer volume of information. However, its exponential growth made the retrieval task increasingly hard, relying in its effectiveness on idiosyncratic and somewhat biased ranking algorithms. To deal with this problem, a “new” web, called the Semantic Web (SW), was proposed, bringing along concepts like “Web of Data” and “Linked Data,” although the definitions and connections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
1
19
0
3
Order By: Relevance
“…The semantic web concept was chosen for analysis because it did not present a stable and consensual definition over time, even in the community directly related to its provenance, the Computer Science field. This condition, verified in previous research [29], confers on the collective construction space a context conducive to the debate and negotiation of different personal perspectives. The existence of the previous study, focused on the statements of the World Wide Web Consortium (W3C) and its director (Berners-Lee) works, allows a comparison between this perspective and that of the editors of the Wikipedia article under analysis.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…The semantic web concept was chosen for analysis because it did not present a stable and consensual definition over time, even in the community directly related to its provenance, the Computer Science field. This condition, verified in previous research [29], confers on the collective construction space a context conducive to the debate and negotiation of different personal perspectives. The existence of the previous study, focused on the statements of the World Wide Web Consortium (W3C) and its director (Berners-Lee) works, allows a comparison between this perspective and that of the editors of the Wikipedia article under analysis.…”
Section: Introductionsupporting
confidence: 77%
“…Another potential relation is to verify if we take into account the descriptions present in the Berners-Lee and W3C publications previously analysed. For this matter, we repeat in Table 3 the content units of the cited study [29]. Referring to the Table 3, we can note that the term "extension" is used to define the Semantic Unlike the definition of the Semantic Web as the "Web of Data", verified in the two sources, we did not find in the definitions of Wikipedia mentions that could be understood as the "Web of Linked Data", as it appears explicitly in two publications in table 3, for 2006 and 2015 (sub-group 2.a.…”
Section: Resultsmentioning
confidence: 99%
“…Another potential relation is to verify if we consider the descriptions present in the Berners-Lee and W3C publications previously analyzed. For this matter, we repeat in Table 4 the content units of the cited study [22].…”
Section: Resultsmentioning
confidence: 99%
“…The semantic web concept was chosen for analysis because we could observe an instability and lack of consensual definitions over time, even in the community directly related to its provenance, the Computer Science field. One previous piece of research, focused on the statements of the World Wide Web Consortium (W3C) and its director, Berners-Lee's works, showed that "the concept of Semantic Web is ambiguous and misinterpreting, given its biasing connection with the term 'semantics' and the association to other terms such as Web of Data, Linked Data or even Web of Linked Data" [22]. The study describes the terminological and conceptual metamorphosis of the definition of semantic web, expressed in the documents analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limitations described above, it is these RDFS-based "light ontologies" that underlie what might be called the "web of linked data" which, although far behind the intended Semantic Web, is a non-negligible achievement [46]. It is also possible to see in this development of the Web a "democratization" of knowledge representation in this digital environment, meeting the original vision of Berners-Lee for it [47].…”
Section: Description Logic Vs Rdf-based Semanticsmentioning
confidence: 99%